2020
DOI: 10.1021/acs.macromol.0c00397
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Y-Shaped Polymer Brushes on Silica Particles and Hierarchical Surface Structures Fabricated by the Coassembly Approach

Abstract: Coassembly of polymer brushes and linear polymers in selective solvents provides a unique method for the fabrication of surface nanostructures on solids. However, some fundamental problems, including the effect of architecture of polymer brushes on the surface coassembly and the thermal dynamic process of the assembly, are left unsolved. To solve the fundamental problems, in this research we synthesized Y-shaped polymer brushes on silica particles and studied the coassembly mechanism of the Y-shaped polymer br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…PEG 107 -b-PS 322 and PS 312 were synthesized by reversible addition−fragmentation chain-transfer (RAFT) polymerization. 33 The degrees of polymerization (DPs) of the polymers were determined by 1 H NMR. Based on size exclusion chromatography (SEC) results, the apparent number-average molecular weights and molecular dispersities of PEG 107 -b-PS 322 and PS 312 were determined to be 39.0 K and 1.29 and 32.8 K and 1.24, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PEG 107 -b-PS 322 and PS 312 were synthesized by reversible addition−fragmentation chain-transfer (RAFT) polymerization. 33 The degrees of polymerization (DPs) of the polymers were determined by 1 H NMR. Based on size exclusion chromatography (SEC) results, the apparent number-average molecular weights and molecular dispersities of PEG 107 -b-PS 322 and PS 312 were determined to be 39.0 K and 1.29 and 32.8 K and 1.24, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…PEG 107 - b -PS 322 and PS 312 were synthesized by reversible addition–fragmentation chain-transfer (RAFT) polymerization . The degrees of polymerization (DPs) of the polymers were determined by 1 H NMR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Silica particles with pyridyl disulfide groups were prepared by using the method reported previously, 46,47 and PS brushes on the silica particles (SiO 2 -PS 80 ) were synthesized by thioldisulfide reaction between PS 80 -SH and pyridyl disulfide groups on the silica particles. The PS grafting density was around 0.6 chains per nm 2 .…”
Section: Synthesis Of Peg-ss-ps and Ps Brushesmentioning
confidence: 99%
“…In previous studies, we reported the fabrication of the nanostructured particle surfaces by coassembly of polymer brushes and free block copolymer (BCP) chains, and a variety of surface nanostructures, including spherical surface micelles, worm-like structures and layer surface structures, were fabricated. 43,46,47 Herein, we report the fabrication of the erasable and rewritable nanostructured particle surfaces formed by coassembly of polymer brushes and linear BCP chains. As shown in Scheme 1, the block copolymer of poly(ethylene glycol) (PEG) and polystyrene (PS) with a disulfide bond at the block point (PEG-SS-PS) is synthesized by reversible addition-fragmentation chain transfer (RAFT) polymerization.…”
Section: Introductionmentioning
confidence: 99%